Characterizing Mission and User Context for Proactive Decision Support. (September 2016) - Brown, Joanna; Fusion, Boston; Bruni, Sylvain; Bennett, Joseph; Fournelle, Connie; Hanna, Christopher; Lucia, Lisa; Ward, Danielle; Woodward, Benjamin
Effective decision support must operate within the proper context view, satisfying potentially complex task demands and fluctuating user capabilities, in support of an overall mission. In response to this need, we are developing an integrated system called Info-Cognitive Proactive Decision Support (InfoCog). InfoCog combines two different perspectives essential for proactive decision support: a data-centered representation of the mission information space and a user-centered representation of the human decision space. InfoCog overcomes the limitations and drawbacks of today's decision support systems that adopt only the information or human decision spaces. We present here a method to characterize the mission information space using a hierarchical probabilistic model combined with multiple hypothesis management. For user characterization, we have developed a user-centric task and cognitive evaluation model. We then combine these complementary perspectives of the current context with predictive capabilities from the mission and user models to anticipate and proactively support future information needs.